Risiko Penyakit Jantung Pada Keluarga Penderita Di Poli Jantung RSUD Dokter Slamet Garut Tahun 2017 - Siti Rosita; Titis Kurniawan; Sandra Pebrianti (JURNAL KESEHATAN BHAKTI HUSADA, 2019)
Coronary Cardiovascular Disease is still one of the major health problems in the world. Prevention can be done with the introduction of risk factors and early detection. Screening is an effective way to identify risk factors for cardiovascular disease in the first stage, furthermore, the offspring's' (siblings) sufferers of cardiovascular disease is one of the risk factors that need to be noticed. This study is aimed to identify the risk level of cardiovascular disease on the patients’ family undergoing outpatient in polyclinic cardiology dr. SlametGarut Hospital. This quantitative descriptive study involves the family (siblings / descendants) of coronary cardiovascular disease patients, with a sample of 89 people, the sampling technique used is accidental sampling. The instrument in this study utilized Cardiovascular Jakarta Score consists of 7 questions divided into ≥5 high, 2-4 medium, and -7 to 1 light. Data were analyzed by frequency distribution and final result. The result showed that almost half of respondents (43.8%) are in medium risk state and few of respondents (29.2%) are in high risk state. This indicated that the proportion of respondents with higher risk is more found in male respondents, aged 60-64 years, has active smoking habit, IMT 26.00-29.99, has no history of DM, TD category of hypertension level 1 and has the habit of less activity. It can be concluded that most families are at risk for coronary cardiovascular disease ≥10% within the next 10 years. Thus it becomes important that families maintain a healthy lifestyle and it is suggested that the hospital develop the program as an effort to raise awareness related to the risk of coronary cardiovascular disease and the importance of prevention efforts towards people who have families with cardiovascular disease.